The effects of disorder in superconducting materials on qubit coherence - Ran Gao; Feng Wu; Hantao Sun; Jianjun Chen; Hao Deng; Xizheng Ma; Xiaohe Miao; Zhijun Song; Xin Wan; Fei Wang; Tian Xia; Make Ying; et al. (Nature Communications)
Abstract Introducing disorder in the superconducting materials has been considered promising to enhance the electromagnetic impedance and realize noise-resilient superconducting qubits. Despite a number of pioneering implementations, the understanding of the correlation between the material disorder and the qubit coherence is still developing. Here, we demonstrate a systematic characterization of fluxonium qubits with the superinductors made by spinodal titanium-aluminum-nitride with varied disorder. From qubit noise spectroscopy, the flux noise and the dielectric loss are extracted as a measure of the coherence properties. Our results reveal that the 1/f α flux noise dominates the qubit decoherence around the flux-frustration point, strongly correlated with the material disorder; while the dielectric loss are largely similar under a wide range of material properties. From the flux-noise amplitudes, the areal density (σ) of the phenomenological spin defects and material disorder are found to be approximately correlated by $$σ \propto {ρ }_{xx}^{3}$$ σ ∝ ρ x x 3 , or effectively $${({k}_{F}l)}^{-3}$$ ( k F l ) − 3 . This work has provided new insights on the origin of decoherence channels beyond surface defects and within the superconductors, and could serve as a useful guideline for material design and optimization.